(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Therapeutic artefacts are commonlyobserved at routine autopsy by the forensic pathologist. It is mostlyproduced during resuscitation and medical intervention. We report two unusual therapeutic artefacts cases i.e. extensive fasciotomy and escharotomy wound artefacts at medico legal autopsy. Extensive fasciotomy was done as a therapeutic measure for compartment syndrome in A 38-year-old male underwent minimal invasive coronary artery bypass surgery for coronary artery disease. During the postoperative period of the second day, the person’s condition suddenly deteriorated and he developed generalized swelling all over the body and was diagnosed with compartment syndrome. The fasciotomy procedure was done and the person died on the same day. The deceased’s relative suspected medical negligence against the treating doctor. The medicolegal postmortem examination was conducted at the Department of Forensic Medicine and Toxicology, AIIMS, New Delhi.